Can laparoscopic common bile duct exploration be performed without any drainage? A propensity score–matched study - Chufa Zheng; Weifeng Wang; Qiquan Peng; Yunheng Peng; Xiaozhong Wang (Videosurgery and Other Miniinvasive Techniques)
Introduction: Although laparoscopic common bile duct exploration (LCBDE) is considered a safe and effective method for treating choledocholithiasis, the absence of any biliary or abdominal drainage during surgery remains controversial.